2006
DOI: 10.1007/s00383-006-1744-2
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic damage in biliary-obstructed rats is ameliorated by leflunomide treatment

Abstract: Cholestasis, or impaired bile flow, occurs in a wide variety of liver diseases and causes hepatic damage by retention and accumulation of toxic hydrophobic bile salts inducing persistent inflammation and oxidative stress. In the present research, we studied the effect of leflunomide, a novel immunosuppressive and anti-inflammatory agent against autoimmune disease, on hepatic damage produced by double ligature of the extrahepatic biliary duct in Wistar Albino rats. Cholestasis was done by double ligature and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
2
27
0
1
Order By: Relevance
“…There is limited information related to antioxidant properties of leflunomide. Karaman et al reported that leflunomide increased the SOD and CAT activity during liver ischemia-reperfusion and biliary obstruction in rats [28,29]. In light of these results, we thought that leflunomide prevented the consumption of antioxidant enzymes by decreasing production of ROS via inhibition of neutrophils accumulation.…”
Section: Discussionmentioning
confidence: 75%
“…There is limited information related to antioxidant properties of leflunomide. Karaman et al reported that leflunomide increased the SOD and CAT activity during liver ischemia-reperfusion and biliary obstruction in rats [28,29]. In light of these results, we thought that leflunomide prevented the consumption of antioxidant enzymes by decreasing production of ROS via inhibition of neutrophils accumulation.…”
Section: Discussionmentioning
confidence: 75%
“…BDL is associated with the development of oxidant injury, hepatic fibrosis, biliary cirrhosis, portal hypertension, and a hyperdynamic circulation that is a dynamic process implying different rates of progres- sion or regression (18). It has been reported that BDL reduces antioxidant defences and increases free radical formation (19). Some studies have suggested the role of free radicals in the modulation of hepatic fibrogenesis, either directly or through lipid peroxidation (20).…”
Section: Discussionmentioning
confidence: 99%
“…Biliary fibrosis is the result of initial hepatocyte injury, with a complex interaction among the inflamatory cells, platelets, Kupffer cells, cytokines and growth factors (21). The cytokines and growth factors are in close relation with oxygen free radicals and inflammation leading to the fibrosis (17,19). In this study, the changes demonstrating bile duct proliferation and fibrosis in expanded portal tracts, including the extension of proliferated bile ducts into lobules, mononuclear cells, and neutrophil infiltration into the widened portal areas, were observed in the BDL group.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme CAT is also most abundant in liver, which catalyses the conversion of H 2 O 2 to corresponding oxygen and water. This enzyme action is reduced due to the presence of peroxides and reactive oxygen species [22] . Increase in concentration of H 2 O 2 in naringintreated groups depicted that there was higher amount of CAT enzyme available in the tissue to decompose the H 2 O 2 with respect to esophagitis control.…”
Section: Resultsmentioning
confidence: 99%